Antiviral Activity of an Ether-Extracted Nonviable Preparation of Brucella abortus - Youngner, J.S. (1974)
Extraction of living Brucella abortus (strain 456) with aqueous ether yielded a nonviable, insoluble residue (Bru-Pel). When injected into mice, Bru-Pel was an effective, nontoxic interferon stimulus. Mice pretreated with Bru-Pel were protected against challenge with otherwise lethal doses of Semliki Forest virus. Significant protection was afforded when Bru-Pel was given as many as 7 days before virus challenge. Evidence is presented dealing with the complex nature of Bru-Pel and with the possibility that the antiviral activity of Bru-Pel may be associated not only with the production of interferon, but with a general increase in the level of nonspecific resistance in animals.